Spectroscopic mode identification of γ Doradus stars: frequencies, modes, rotation and wave leakage. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Pollard, Karen R.; Brunsden, E.; Davie, M.; Greenwood, A.; Cottrell, P. L.
Abstract: The gravity modes present in γ Doradus stars probe the deep stellar interiors and are thus of particular interest in asteroseismology. The MUSICIAN programme at the University of Canterbury has been successfully identifying frequencies and pulsation modes in many γ Doradus stars using hundreds of precise, high resolution spectroscopic observations obtained with the 1.0 m telescope and HERCULES spectrograph at the Mt John Observatory in New Zealand. In this paper we present a summary of our spectroscopic frequency and mode identifications. Of particular interest from our spectroscopic analyses are: the prevalence of (ℓ, m ) = 1, 1 modes in many γ Dor stars; the importance of stellar rotation in the interpretation of the frequency and mode identification; and finally, possible evidence of wave leakage in one of these stars.